The Diversity of Wood and Non-Wood Forest Products: Anatomical, Physical and Chemical Properties, and Potential Applications - Sousa, Vicelina; Pereira, Helena; Quilhó, Teresa; Miranda, Isabel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The diversity of wood and non-wood forest products is enormous and reflected in their anatomical, physical and chemical properties as well as their potential applications. Special attention should be given to lesser-known species and even to invasive species, which may be profitable when properly managed, thereby decreasing the overexploitation of threatened species. Besides the market importance of stem wood, other tree components and non-wood forest products, often regarded simply as forest residual materials, are valuable forest resources with various potential applications that can strengthen the circular economy. Assessing the characteristics of these diverse materials, such as their structure and anatomy as well as their physical and chemical properties, is fundamental for evaluating their potential and increasing high-quality end-uses. This knowledge will also contribute to sustainable forest management with enhanced forest diversity and species conservation in addition to the reinforcement of certification and environmental policies.